2006
DOI: 10.1103/physrevb.73.214508
|View full text |Cite
|
Sign up to set email alerts
|

Role of charge doping and lattice distortions in codopedMg1x(AlLi)xB2<

Abstract: We prepared a series of Mg 1−x ͑AlLi͒ x B 2 samples with 0 ഛ x ഛ 0.45 in order to compensate with Li the electron doping induced by Al. Structural characterization by means of neutron and x-ray diffraction confirms that Li enters the MgB 2 structure even though in an amount less than nominal one. We performed susceptibility, resistivity, and specific heat measurements. Vibrational properties were also investigated by means of Raman spectroscopy. We compare these results with those obtained on a homologous seri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 36 publications
6
47
1
Order By: Relevance
“…[27,28] It is apparent from Figure 6 that with decreasing x, the 730 cm -1 peak increases in intensity relative to the 600 cm -1 peak. A compilation of various property measurements is shown in Figure 7 and this allows a general picture of the relation of stoichiometry to properties to emerge.…”
Section: Full Papermentioning
confidence: 97%
See 1 more Smart Citation
“…[27,28] It is apparent from Figure 6 that with decreasing x, the 730 cm -1 peak increases in intensity relative to the 600 cm -1 peak. A compilation of various property measurements is shown in Figure 7 and this allows a general picture of the relation of stoichiometry to properties to emerge.…”
Section: Full Papermentioning
confidence: 97%
“…These features have been observed in Al-doped samples and have been associated with structural disorder. [27][28][29] The appearance of more than one phonon peak further implies the violation of Raman selection rules induced by disorder resulting in a modified …”
Section: Full Papermentioning
confidence: 99%
“…Moreover, disorder introduced by doping might enhance interband scattering, also as an effect of structural deformations, and does not allow us to carefully identify the real reasons for the changes in the superconducting properties. These problems can be overcome either by co-doping, as attempted with a substitution of lithium and aluminium on Mg sites by Monni et al 12 that, nevertheless, did not obtain a complete charge balance, or by particles irradiation.…”
Section: Introductionmentioning
confidence: 96%
“…Due to the anisotropic character of MgB 2 , single crystal studies provide a more detailed insight and such studies have been reported for C, Al, and Mn substitutions. [18][19][20][21][22][23] Other substitutions, such as Li 24,25 and co-substitutions with Al and Li 26,27 were investigated on polycrystalline samples or polycrystalline thin films.…”
Section: Introductionmentioning
confidence: 99%